Optimum autofrettage pressure in thick cylinders - Ayob, Amran; Elbasheer, M. Kabashi (Faculty of Mechanical Engineering, 2007)

(untitled)
In optimal design of pressurised thick-walled cylinders, an increase in the allowable internal pressure can be achieved by an autofrettage process. An analysis is carried out on plain cylinders by using the von Mises and Tresca yield criteria to develop a procedure in which the autofrettage pressure is determined analytically, resulting in a reduced stress distribution. A validation by a numerical simulation shows that the analytical and numerical simulations correlate well in terms of trend and magnitude of stresses.